Contingency in international law : on the possibility of different legal histories - Venzke, Ingo; Heller, Kevin Jon (Oxford : Oxford University Press, 2021)
This volume brings together a group of renowned experts to discuss the question of whether international law could have developed differently. Contributors explore contingency in theory and practice across a range of fields, including those related to migrants and refugees, the sea and natural resources, and human rights.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 30, 2021).
Keywords: International law; Contingency (Philosophy); Law; International law